Popularity Among Peer Role Models: A Moderator of Peer Victimization and Depressive Symptoms. (February 2020) - Luo, Tana; Schwartz, David; Malamut, Sarah; Mali, Luiza V.; Ross, Alexandra C.; Duong, Mylien T.; Badaly, Daryaneh
This short-term, longitudinal study examines evidence that the level of popularity among adolescents' peer role models exacerbates the emotional impact of mistreatment by peers. We recruited 469 adolescents (255 boys, 214 girls;X ¯ age = 12.7 years) from an ethnically diverse middle school and followed these youth for a 1-year period. We collected identical measurement batteries in two consecutive waves. Participants completed a self-report assessment of depressive symptoms, as well as a peer-nomination inventory identifying victimized and popular classmates. The inventory also included items asking adolescents to identify peers they want to be like, respect, and admire. High popularity levels among peer role models were associated with intensified associations between peer victimization and depressive symptoms. However, these findings held only for boys. Taken together, these results suggest that victimization by peers is most detrimental for adolescent boys who seek to identify with their more socially dominant classmates.